Solvency Analysis on Indonesia's External Debt - Nasir, Mohamad (Badan kebijakan Fiskal, 2014)
During Periods 2010-2013, Indonesia had economic growth. However, external debt had also inreased an reached USD265 billion in 2013, Indeed, this achievement raises a question, what the solvency level of indonesia's external debt is. By using Debt Sustainable Framework (DSF) method developed by Bretton Woods Institution (BWI), it can be known. Based on sample data in 2012 and calculation result, it can be known that form 6 DSF indicators Indonesia had 2 red indicators. They are debt service to export ratio and debt service to budget revenue ratio. The two indicators showed that Indonesia's solvency has risk regarding liquidity capability, and a limited fiscal support in the case Government do an intervention for external debt condition. Some main recommendations are proposed in this paper. Some o them are: 1) to improve liquidity or availability of foreign currency (USD), 2) to manage external debt of nonfinancial enterprises and no SOSEs, and 3) to increase export and decrease import.